Factors influencing behavioral intention of farmers to use ICTs for agricultural risk management in Malaysia - Ali, Muhammad; Man, Norsida; Muharam, Farrah Melissa; Omar, Siti Zobidah (Pakistan Agricultural Research Council, 2020)
The primary aim of this research was to examine the factors influencing behavioral intention of farmers to use ICTs for agricultural risk management. The past research reveals that many researchers had tried to determine factors affecting behavioural intentions of the respondents and TPB has been applied as technology acceptance model in various contexts. However, predicting behavioral intentions to use ICTs for agricultural risk management has not been evaluated from the actual field. Therefore, the data were collected from 360 farmers through multistage cluster sampling technique. Multiple linear regression through SPSS was administered for statistical procedure. The findings confirmed that the theory (TPB) was statistically feasible to predict behavioral intention of farmers to use ICTs for agricultural risk management. The results further reveal that attitude was one of the most influenced of intention, which was followed by perceived behavioral control and lastly the subjective norms. Thus, using TPB in this context would be helpful for other researchers and academia to understand the influence of each construct in the model.